2005
DOI: 10.1111/j.1440-1746.2005.03919.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of hepatocellular carcinoma with extrahepatic metastases

Abstract: Extrahepatic metastases of HCC are not rare. The possibility of extrahepatic metastases and the clinical features of extrahepatic metastases should be considered when examining patients with HCC, particularly those with advanced intrahepatic tumors, to enable precise evaluation of the spread of HCC and determination of the appropriate treatment method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
452
5
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 458 publications
(485 citation statements)
references
References 14 publications
22
452
5
6
Order By: Relevance
“…The incidence of HCC is increasing in countries where hepatitis B or C virus is endemic [6]. The present study enrolled a relatively large number of patients with bone metastases from HCC and showed better detectability of FDG PET/CT than bone scintigraphy.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The incidence of HCC is increasing in countries where hepatitis B or C virus is endemic [6]. The present study enrolled a relatively large number of patients with bone metastases from HCC and showed better detectability of FDG PET/CT than bone scintigraphy.…”
Section: Discussionmentioning
confidence: 69%
“…Bone metastasis from HCC is not uncommon, and the incidence has been increasing [5,6]. A recent study reported that patients with isolated bone metastasis showed longer survival than those with metastases in bone and other sites [7].…”
Section: Introductionmentioning
confidence: 99%
“…Uka et al stated that extrahepatic metastases from HCC most commonly occur in the lungs (47%), lymph nodes (45%), bones (37%), and adrenal glands (12%) [1] , while Natsuizaka et al reported that they tend to arise in the lungs (53.8%), bones (38.5%), lymph nodes (33.8%), and adrenal glands (16.9%) [2] . In addition, Jung et al found that most metastases occurred in the lungs (55%), lymph nodes (46.7%), bones (20.4%), and adrenal glands (7.5%) [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Extrahepatic metastases in patients with HCC are becoming more common due to improved diagnostic methods and prolonged survival [ incidence of extrahepatic metastases in HCC patients is 15.2% and 13.5%, respectively [1,2] . Uka et al stated that extrahepatic metastases from HCC most commonly occur in the lungs (47%), lymph nodes (45%), bones (37%), and adrenal glands (12%) [1] , while Natsuizaka et al reported that they tend to arise in the lungs (53.8%), bones (38.5%), lymph nodes (33.8%), and adrenal glands (16.9%) [2] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation